Російські фортеці на території Запорожжя як флотські бази: зберігання суден Дніпровської флотилії у 1740-х рр. - Сухомлин, О. (Чорноморська минувшина, 2021)
Розглянуто малодосліджений аспект історії російських фортець на території Запорожжя доби Нової Січі – зберігання плавзасобів ліквідованої Дніпровської флотилії після закінчення російсько-турецької війни 1735–1739 рр. На основі документальних джерел фонду 59 «Київська губернська канцелярія» Централь- ного державного історичного архіву України у м. Києві зроблено спробу встановити кількість плавзасобів Дніпровської флотилії (байдаків), які зберігалися в Усть-Самарському ретраншементі. Шляхом порівняння даних з кількох облікових джерел підтверджено факт наявності у вказаній фортеці законсервованих байдаків. По- казано, що встановлення точної кількості плавзасобів ускладнене специфікою джерельної бази. Проте можна стверджувати, що до 1745 р. у ретраншементі зберігалося щонайменше 30 байдаків. Подальша розробка окресленої у розвідці проблематики дозволить не лише дослідити спектр функцій російських фортець на теренах Запорожжя, а й глибше розкрити повсякденні взаємовідносини російських залог з козаками й посполитими (торговельні стосунки, асортимент обміну тощо). Studies of Russian military presence in the lands of Zaporozhia during the New Sich era (1734–1775) pay relatively little attention to the uses of Russian fortresses between the Russo- Turkish wars of 1735–1739 and 1768–1774. From 1739 to 1768 the military importance and defense capability of the Russian fortresses diminished, thus their main purpose shifted to information gathering on the Russian-Ottoman borderlands and the Zaporozhian Host of the Lower Dniper itself. Furthermore, another quite understudied function of these fortresses was to serve as military depots, both acting and reserve. This article concentrates on the understudied aspect of the history of Russian fortresses and the Zaporozhia lands during the New Sich era – the storage of vessels of the liquidated Dnieper flotilla after the Russo-Turkish war of 1735-1739. The primary source base for this article consists of the documents from “Kyiv Provincial Chancellery” (Central State Historical Archive of Ukraine, fund 59). The Ust’-Samara retrenchment was a main naval base of the Dnieper flotilla located at the mouth of the Samara River (present-day Dnipro). The reorganization of the Dnieper flotilla material base and fleet supplies took several years after the end of the 1735-1739 war. Subsequently, various fleet supplies (military vessels; ship equipment like ropes, blocks, oars, flags, anchors; naval artillery and related supplies; tools for ships repairs and maintenance like "konopatky"; building materials, ship nails, resin; food stocks for ship crews, etc) were stored in the special fortress warehouses. However, storage conditions were inadequate, naval depots could be destroyed, while equipment and watercraft could be stolen by the Russian officers to be resold later. Relying on documentary sources, an attempt was made to clarify the number of Dnieper flotilla vessels, that were stored in the Ust’-Samara retrenchment. To that end, the article introduces into scientific circulation a document that most fully reflects the number of military vessels, stored at the Russian fortresses in Zaporozhia as of November 1, 1742 - a report compiled by Captain I. Stepanov at the request of the Ust’-Samara retrenchment commander A. Chichagov, commander of all Russian fortresses in Zaporozhia. At that time, the total number of vessels (both suitable and unsuitable for use) amounted to 350. These vessels were stored in the Kamianskyi, Khortyts’kyi, Malyshevs’kyi and Nenasytets’kyi retrenchments. Comparison of data from several documents reveals that for unknown reasons this number (350) did not include boats stored in the Ust’-Samara retrenchment. This article further indicates that the study of exact number of the vessels is complicated by the specifics of the source base. Further elaboration of the issues outlined in the present article would allow not only to explore the functions of Russian fortresses in Zaporozhia during the New Sich era and their role as centers of the Russian military presence, but would also reveal the everyday relations of Russian soldiers with the Cossacks and the peasants (“pospolyti”). The crucial need to study original documentary sources on the history of Russian fortresses in Zaporozhia is emphasized once more.